2005
DOI: 10.1111/j.1365-2621.2005.tb11450.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Characteristics of Enhancement Solutions

Abstract: ev oducts and to ev oducts and to ev oducts and to ev oducts and to evaluate the effect of potentially lethal temper aluate the effect of potentially lethal temper aluate the effect of potentially lethal temper aluate the effect of potentially lethal temper aluate the effect of potentially lethal temperatur atur atur atur atures es es es es. E . E . E . E . Enhancenhance-nhance-nhancenhancement solutions w ment solutions w ment solutions w ment solutions w ment solutions wer er er er ere pr e pr e pr e pr e pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…They concluded that diacetate and lactate appeared to be synergistic resulting in greater antimicrobial action than can be achieved with either additive by itself. However Wicklund et al [25] found that addition of both lactate and diacetate to a salt/phosphate enhancement solution resulted in the greatest reduction of E. coli K12, followed by lactate. Many researchers [26][27][28][29] suggested that to improve the microbiological quality of the meat by application of anti-microbial which result in:…”
Section: Spoilage and Pathogenic Microorganismsmentioning
confidence: 99%
“…They concluded that diacetate and lactate appeared to be synergistic resulting in greater antimicrobial action than can be achieved with either additive by itself. However Wicklund et al [25] found that addition of both lactate and diacetate to a salt/phosphate enhancement solution resulted in the greatest reduction of E. coli K12, followed by lactate. Many researchers [26][27][28][29] suggested that to improve the microbiological quality of the meat by application of anti-microbial which result in:…”
Section: Spoilage and Pathogenic Microorganismsmentioning
confidence: 99%
“…E. coli K‐12 showed a very low susceptibility at the minimal exposure time to the enhancement solution, with or without sodium lactate, prior to the PEF treatment (data not shown). The susceptibility of E. coli to enhancement solutions with or without sodium lactate has already been reported by Wicklund et al. (2005).…”
Section: Resultsmentioning
confidence: 60%
“…McWilliam and Stewart (2002) found no antimicrobial activity of 1.12% lactic acid on two E. coli strains after 8 h of treatment at 5C, a temperature used during processing in meat plants. In another study, Wicklund et al. (2005) detected less than 1 log reduction of Escherichia coli K‐12 in enhancement solutions containing 3% sodium lactate, after 1 min at 4C.…”
Section: Introductionmentioning
confidence: 95%
“…Sodium diacetate in conjunction with sodium lactate has been shown to have a synergistic effect on controlling the growth of Listeria monocytogenes in vacuum‐packed cervelat sausage and cooked ham (Blom and others 1997). In a recent study, an enhancement solution containing sodium diacetate and sodium lactate inoculated with 6 log 10 CFU/mL E. coli K12 was found to produce the greatest reduction in viable cell counts, followed by an enhancement solution containing lactate alone, when compared to a typical salt and phosphate solution and water (Wicklund and others 2005).…”
Section: Introductionmentioning
confidence: 99%